Impact of Front Line Demonstrations of INM in Okra During Off Season in the Dang District of Gujarat - Aklade, S. A.; Dobariya, J. B.; Thesiya, N. M. (International Journal of Economic Plants, 2018)
Okra is the major vegetable crops grown in the Dang district of Gujarat state especially during the rabi season which can be consider as off season as okra is the main crop of kharif and summer season. One of the major constraints of low productivity of okra may be due to partial adoption of recommended package of practices by the growers. So, to address the yield gap, the front line demonstrations on integrated nutrient management (INM) along with scientific package of practices in okra were conducted for three consecutive years from 2012-13 to 2014-15 on farmer’s field in different villages of the Dang district. Prevailing farmers’ practices were treated as control for comparison with recommended practices. In the three years data, it was observed that due to adoption of INM along with scientific package of practices, average yield of 96.0 q ha-1 was obtained in demonstrated plot over 83.7 q ha-1 in control plots with an additional yield of 12.3 q ha-1 and increasing the average productivity of okra by 14.8%. The average extension and technology gap were found to be 11.0 and 24.0 q ha-1, respectively with the technology index of 20.0% during the demonstration years. Besides this, the demonstrated plots gave higher gross return of Rs. 1,13,533.00 ha-1, net return of Rs. 71,300.00 ha-1 with higher benefit cost ratio of 2.69 as compared to farmer’s practice during the three years of study.